BMD in elite female triathletes is related to isokinetic peak torque without any association to sex hormone concentrations - Wulff, H. E.; Melin, A.; Waaddegaard, M.; Kanstrup, I.-L. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: Female endurance athletes suffering from low energy availability and reproductive hormonal disorders are at risk of low BMD. Muscle forces acting on bone may have a reverse site-specific effect. Therefore we wanted to test how BMD in female elite triathletes was associated to isokinetic peak torque (IPT) and reproductive hormone concentrations (RHC). A possible effect of oral contraceptives (OCON's) is taken into consideration. METHODS: Eight female elite triathletes (training 8-24 hrs/wk) and seven sedentary controls, age 21-37 years, participated. Total body and regional BMD (g.cm-2) were measured by DXA. IPT were measured during knee extension, and trunk extension and flexion (Nm). Serum RHC and biochemical bone markers were evaluated. Energy balance was estimated from 7-days training-and weighed food records. RESULTS: Despite a high training volume, BMD in triathletes was not higher than in controls. In triathletes trunk flexion IPT, but not RHC, was a strong predictor of BMD in both total body and femur (0.70<r<0.86, P<0.05). RHC did not differ between triathletes and controls, but in OCON-users RHC (in controls also BMD) seemed lower than in non-users. Energy intake in triathletes corresponded to 65-111% of energy expenditure. CONCLUSION: The association between trunk flexion IPT and BMD in triathletes supports the theory that muscle forces are important osteogenic factors. The findings of no correlation between RHC and BMD, but a tendency to a negative effect of low RHC only in OCON-controls, might indicate that in female athletes muscle forces acting on bone potentially counteract a negative effect of reproductive hormonal disorders on BMD.